Zingiber Officinale Rosc. (Shunthi): A Crossroad of Tradition and Modern Pharmacology - Goldi Singh; Premlata; Pooja Chaurasiya; Anil Kumar Singh; Poonam Sharma (International Journal of Ayurveda and Pharma Research, 2025)
Objective: This article aims to reveal the ancient classical uses of Shunthi for maintaining better health and management of various health illnesses. Data Source: The data on Shunthi (dried ginger) has been systematically gathered from authoritative Ayurvedic classical texts, including Samhitas and Nighantus, as well as from reputable scientific sources such as PubMed and Google Scholar. Review Methods: This article reveals the ancient resourcefulness behind the therapeutic uses of Shunthi from traditional system of medicine to contemporary science. The traditional uses of Shunthi confirms the ayurvedic principles described in Ayurvedic classical texts from Vedic era to till. Conclusion: In this review work, it was found that Shunthi overcomes various diseases related to immune system, digestive system, nervous system and circulatory system. Different herbal, herbomineral and polyherbal formulations of Shunthi have used to maintain the health of individual.